Archangel's kiss - Singh, Nalini, 1977- (Singh, Nalini, 1977- Guild Hunter series., 2010)
When her lover, the archangel Raphael, receives an invitation to a ball from the archangel Lijuan, Elena, who is still recovering from her transformation into an angel, must accompany him to Beijing, where a nightmare awaits them.